Peningkatan Hasil Belajar Matematika dengan Model Pembelajaran Numbered Heads Together - Mizaniya, Mizaniya; Rokhimawan, Moh. Agung (Mitra PGMI: Jurnal Kependidikan MI, 2021)
This study aimed to describe the implementation of the cooperative learning model of Numbered Heads Together (NHT) to improve mathematics learning outcomes. This research was a participatory and collaborative classroom action research conducted between researchers and teachers. The research subjects were teachers and 28 students grade IV A students at MI Al-Huda Karangnongko Yogyakarta. Data have been collected through observation, interviews, tests, and documentation, those further analyzed using quantitative and qualitative descriptive analysis. The results showed that learning mathematics using the NHT model could improve students' learning outcomes. This was indicated by an increase of learning outcomes percentage by 10.71% in pre-action, 53.57% in cycle I, and 92.86% in cycle II. The increase in the average of the evaluation test in the pre-action was 55.36 with the lowest score was 0 and the highest was 80, the first cycle was 72.86 with the lowest score was 0 and the highest was 100. The second cycle was 89.64 with the lowest score was 50 and the highest was 80 by minimum completeness criteria was 75. Therefore, NHT could improve students' mathematics learning outcomes.